Food system analysis and the development of a system dynamics approach to improve food security for a vulnerable community in the Breede River Region, Western Cape Province, South Africa - Roos, Johanna Adriana (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2012.